Influence of Energy Density on the Anisotropy of Multi-Property Behaviour in Additively Manufactured Fe-Si Alloys - Babu, Gokul (My University, 2025)
The influence of volumetric energy density (VED) on the anisotropic magnetic, mechanical, and electrical properties of Fe–6.5 wt.% Si alloys fabricated by Powder Bed Fusion–Laser (PBF-L) was investigated. Laser power and scan speed were systematically varied while keeping other process parameters constant. Characterization by VSM, XRD, Vickers hardness (HV), electrical resistivity, and optical microscopy revealed pronounced anisotropy between the X–Z and X–Y planes. Samples produced at optimal VED showed higher saturation magnetization (Ms) and lower coercivity (Hc) along the build direction (BD), while variations in hardness and resistivity reflected the combined effects of residual stress and solidification dynamics. Optimizing VED effectively controls anisotropy in the multi-property response of PBF-Lprocessed Fe–6.5 wt.% Si, providing insights into process parameters for fabricating high-performance magnetic components for electric machine applications
Keywords: Additive Manufacturing; PBF-L; VED; Fe–Si Alloys; Anisotropy; Magnetic Properties; Mechanical Properties; Electrical Resistivity